Regulatory subunits of cAMP-dependent protein kinases are degraded after conjugation to ubiquitin: a molecular mechanism underlying long-term synaptic plasticity. - Hegde, A N (1993)
In Aplysia, behavioral sensitization of defensive reflexes and the underlying presynaptic facilitation of sensory-to-motor neuron synapses lasts for several minutes (short term) or days to weeks (long term). Short-term sensitization has been explained by modulation of ion-channel function through cAMP-dependent protein phosphorylation. Long-term facilitation requires additional molecular changes including protein synthesis. A key event is the persistent activation of the cAMP-dependent protein kinase at baseline concentrations of cAMP. This activation is due to selective loss of regulatory (R) subunits of PKA without any change in catalytic (C) subunits. To understand the molecular mechanisms that produce the loss of R subunits in long-term facilitation, we investigated how R subunits are degraded in extracts of Aplysia nervous tissue and in rabbit reticulocyte lysates. Degradation of Aplysia R subunits requires ATP, ubiquitin, and a particulate component that appears to be the proteasome complex. Degradation is blocked by hemin, which causes the accumulation of high molecular weight derivatives of R subunits that are likely to be ubiquitin conjugates of R subunits and intermediates in the degradative pathway. We also show that vertebrate RI and RII subunits can be degraded through the ubiquitin pathway. We suggest that degradation is initiated by cAMP, which causes the holoenzyme to dissociate and, further, that the altered R-to-C ratio in Aplysia sensory neurons is maintained in long-term facilitation by newly synthesized proteins that help target R subunits for accelerated degradation.